Carregar o Peso eterno: uma tragédia familiar em julgamento no tribunal do júri se São Carlos-SP - Bastos, Felipe Benhur Nascimento (Universidade Federal de São Carlos, 2023)
This paper aims to understanding and analyzing the moral discourses that are articulated by actors of law in a judgment that results in acquittal in the Trial by Jury. For this purpose, the content of these speeches and how they are articulated, an ethnographic description of a case that was judged by the Trial by Juri of São Carlos-SP. Besides analysis of excerpts from the process of the same case, searching to understand the meaning of a judgment that is perceived, at the same time, as legal and moral, and decides for the acquittal of the person tried.
Carrying the eternal weight: a family tragedy on trial in the jury court in São Carlos-SP
Keywords: Tribunal do júri; Absolvição; Aulgamento moral; CIENCIAS HUMANAS::SOCIOLOGIA